Pemanfaatan Media Internet Dalam Mendukung Kinerja Penyuluh Pertanian Pada Pengembangan Kakao Di Luwu Utara - Mutia Rahmaniah; Sapar Sapar; Anggra Alfian (JURNAL AGRICA, 2023)
Using Internet media is an alternative to support the performance of agricultural extension workers. The purpose of this study was to analyze the influence of internet media in supporting the performance of agricultural extension agents on cocoa development in North Luwu. The population used in this study were agricultural extension workers who worked at the sub-district BPP in North Luwu Regency. This research uses a descriptive, explanatory method with a quantitative approach. The method used to analyze this research uses Structural Equation Modeling (SEM) based on variants. The results showed that the use of internet media had a positive and insignificant relationship to the performance of agricultural extension workers, and the performance of agricultural extension services had a positive and insignificant relationship to the behaviour of farmers in North Luwu Regency. The performance of the agricultural extension officers, achievements, or ability to work using internet usage patterns, stated that the research described the quality provided by the agricultural extension agents in the SEM analysis. In addition, the perceptions of farmer extension workers and the internet media show positive perceptions. Most respondents think it is useful for them in searching for information and that Information and Communication Technology are easy to learn.